Lokakarya Kurikulum Merdeka Belajar Pada Sekolah Penggerak Di Sumba Timur NTT - Engelbertus Nggalu Bali; Angelikus Nama K (Universitas Nusa Cendana, 2023)
The freedom to learning curriculum is a catalyst for transformation and acceleration efforts in improving the quality of early childhood education. The concept of independent learning and independent play is the design of learning activities that are able to develop the child's development phase as a whole. However, in reality school principals and teachers still experience difficulties in implementing the independent curriculum in the phonation phase (PAUD). This workshop activity was carried out for all partners in the East Sumba and Central Sumba district drive school programs, totaling 6 units. This workshop activity aims to train principals and teachers regarding the flow of implementing the independent learning curriculum. Through workshop activities, the entire ecosystem is able to understand the curriculum, both substance and technique. The method used in this workshop is through a preliminary study, method identification stage, implementation stage and evaluation stage. The independent learning curriculum contains learning outcomes (CP), learning objectives (CP), learning objectives flow (ATP) and teaching models. Through this workshop activity, the entire ecosystem of partner schools for the driving school program is able to understand and implement it in learning activities.